Cultivating nutrition: exploring participants’ perspectives on nutrition gardens and nutrition education program in rural Tamil Nadu and Odisha, India - Jaleel, Abdul; Chukkala, SuryaGoud S.; Sriswan, Raja; Panda, Hrusikesh; Singnale, Pooja; Meshram, Indrapal I.; Avula, Laxmaiah; Hariharan, G. N.; Arlappa, Nimmathota; Gavaravarapu, SubbaRao M. (Frontiers in Sustainable Food Systems, 2025)
Malnutrition persists as a critical public health concern in India, aggravated by widespread nutrition insecurity due to lack of dietary diversity. Integrating the promotion of nutrition gardens with nutrition education offers a promising strategy to mitigate these challenges, particularly among vulnerable populations. This paper examines the perceptions of households participated in an intervention to promote nutrition-sensitive agriculture and improve nutrition education to combat undernutrition in small-scale farming households in rural India. Using a mixed-methods approach, data were collected from participants in Tamil Nadu and Odisha through structured interviews, key informant interviews, and focus group discussions. The qualitative data were thematically analysed, and a SWOT analysis was conducted to assess the intervention’s strengths, weaknesses, opportunities, and threats. The findings show that by integrating nutrition-sensitive approaches into agricultural activities, the intervention has transformed traditional home gardening practices by diversifying homegrown produce. Participants highly valued the training sessions, and the provision of seeds and saplings, which facilitated the establishment of nutrition gardens and improved nutrition-related knowledge. However, while many participants reported improved nutrition knowledge, improvements in dietary diversity and overall nutrition were less commonly reported. Achieving a sustained impact will require context-sensitive implementation, sustained engagement, and addressing structural barriers.